(untitled) - Spielvogel, Jackson J. (Belmont, CA, 2002)
This brief version of Western Civilizaiton retains all of the best-selling features of the larger book in a condensed format. Three versions are available: Comprehensive (Chapters 1-29), Volume I: To 1715, and Volume II: Since 1500. The author writes, "I began this project with two primary goals. First, I wanted to write a well-balanced work in which the political, economic, social, religious, intellectual, cultural, and military aspects of Western civilization would be integrated into a chronologically ordered synthesis. Second, I wanted to avoid the approach that is quite common in other brief histories of Western civilization - an approach that makes them collections of facts with little continuity from section to section. Instead, I sought to keep the story in history. Narrative history effectively transmits the knowledge of the past and is the form that best enables students to remember and understand the past. At the same time, I have not overlooked the need for the kind of historical analysis that makes students aware that historians often disagree in their interpretations of the past."
Keywords: Civilization, Western; History